2015
DOI: 10.1007/s13277-015-3289-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of SRPK1 on glioma apoptosis, metastasis, and angiogenesis through the PI3K/Akt signaling pathway under normoxia

Abstract: Gliomas, the most common primary brain tumors, have low survival rates and poorly defined molecular mechanisms to target for treatment. Serine/arginine SR protein kinases 1 (SRPK1) can highly and specifically phosphorylate the SR protein found in many tumors, which can influence cell proliferation and angiogenesis. However, the roles and regulatory mechanisms of SRPK1 in gliomas are not understood. The aim of this study was to determine the functions and regulation of SRPK1 in gliomas. We found that SRPK1 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…It has been reported that the HP gene is relevant to IA, but few previous studies have reported the correlation between SRPK1 and IA. However, in some other tumor diseases, it has been reported that SRPK1 affects progression of diseases through the PI3 K/AKT signaling pathway . In addition, it was also reported that the AKT signaling pathway was involved in the progression of aneurysms, but have not yet been demonstrated in IA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the HP gene is relevant to IA, but few previous studies have reported the correlation between SRPK1 and IA. However, in some other tumor diseases, it has been reported that SRPK1 affects progression of diseases through the PI3 K/AKT signaling pathway . In addition, it was also reported that the AKT signaling pathway was involved in the progression of aneurysms, but have not yet been demonstrated in IA.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some other tumor diseases, it has been reported that SRPK1 affects progression of diseases through the PI3 K/AKT signaling pathway. [24][25][26] In addition, it was also reported that the AKT signaling pathway was involved in the progression of aneurysms, 27,28 but have not yet been demonstrated in IA. In summary, our results suggested that SRPK1 may affect the progression of IA by regulating the PI3 K/AKT signaling pathway.…”
Section: Srpk1 and The Pi3 K/akt Signaling Pathway Are Related To Tmentioning
confidence: 99%
“…4,30,31) Furthermore, previous studies have demonstrated that BDNF promotes cell proliferation and migration through the PI3K/Akt pathway. 32) Moreover, insulin receptor substrate-4 (IRS-4) enhances cell migration via the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The plexin-B1/SRPK1 pathway regulates cell motility, apoptosis, and angiogenesis [69] ↑SRPK1 was found in glioma cell lines ↓SRPK1 suppressed cell viability and response to chemotherapy in vitro [52] ↑SRPK1 was found in glioma cell lines ↓SRPK1 suppressed apoptosis in vivo and in vitro, also migration and invasion in vivo SRPK1 interacts with the PI3K/Akt pathway and modulates the expression of MMP-2 and MMP-9 [70]…”
Section: ↓Srpk1 Suppressed Migration and Invasion In Vitromentioning
confidence: 99%